This preview has intentionally blurred sections. Sign up to view the full version.
View Full Document
Unformatted text preview: = X (W+X)(W+Y)(W+Z) = X (W+Y)(W+Z) f. A+BC+DE = (A+BD+D)(A+BC+E) = (A+B+D)(A+D+D)(A+B+E)(A+C+E) = (A+B+D)(A+B+E)(A+C+E) 2.8 Simplify the following expressions to a minimum sum of products: a. [(AB)’+C’D]’ = ((AB)’+C’D)’ = ((AB)’)’ . (C’D)’ = AB.(C+D’) = ABC + ABD’ Obtain the sum of products of (A+B’)(A+C+D)(A+B’+D) D B C B A D C B A B A D C A D B A D C A B A + + = + + = + + + = + + + + + ) ( ) )( ( ) )( )( ( X B X A X B A = = = + Obtain the sum of products of (A+B’)(A’+C)(C+D)(B+D) D A BC BC D BC A D B D C C A B A + = + + = + + + + ) )( ( ) )( )( )( ( X BC =...
View
Full Document
 Spring '10
 NIGELJOHN
 Addition, Summation

Click to edit the document details